Economic Order Quantity Method Used In The Inventory Control System Of Agung Store - Harahap, Muhammad Rifai; Alda, Muhamad (UIN Sumatera Utara Medan, 2025)
The objective of this investigation is to enhance inventory management at Toko Agung by implementing the Economic Order Quantity (EOQ) method. The System Development Life Cycle (SDLC) methodology was employed to develop a web-based inventory control system that integrates EOQ principles into daily operational processes. The system is designed to determine the optimal order quantities, reorder points, and safety stock levels in order to minimize the total inventory costs, which include both ordering and holding expenses. By applying EOQ calculations, the system assists in balancing procurement frequency and stock levels to avoid unnecessary capital tie-up or shortages. The findings reveal that the implementation of EOQ led to a 15% reduction in total inventory-related costs, a significant improvement in stock availability, and a 10% decrease in the risks of overstock and stockouts. Furthermore, the automation of the procurement process through the system enabled more accurate forecasting and timely decision-making. These results demonstrate that the integration of EOQ into a web-based inventory system can significantly improve the efficiency, accuracy, and cost-effectiveness of inventory management in retail business operations.